Diabetes Mellitus asociada a pancreatitis autoinmune: Caso Clínico. - Pinto K, Esteban; Vargas R, Cecilia; Gómez G, Patricia; Durruty A, Pilar; López S, Gloria (Revista Médica de Chile, 2019)
Autoimmune pancreatitis is uncommon, responds to steroids and is usually associated with diabetes mellitus. We report a 73 years old male who, two months after a diagnosis of diabetes mellitus, presented with obstructive jaundice and weight loss. Abdominal magnetic resonance imaging was suggestive of an autoimmune pancreatitis and serum IgG4 was 339 mg/dl (normal range 3-201). The patient was treated with prednisone 40 mg/day with a good clinical and laboratory response. During outpatient care, the dose of prednisone was tapered.